Applying Lean in Hypermarkets - Bobrytskyy, Serhiy; Martínez, Felipe; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2017)
This Bachelor Thesis focuses on the determinants of hypermarkets and areas for lean and operational management application. The goal of the thesis is to determine the applicability of lean and operational management tools in hypermarkets. The method of the analyses is the critical case study using the deductive approach. The theoretical part explains the main factors forming hypermarket and the main lean tools which can be applied for this topic. The practical part includes the different analyses of the observed hypermarket and the possible ways to improve the current situation there, using the lean management. The output of the thesis is the project for improvement, which can be used for the real-life application.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses